Charge density alterations in human hair fibers: An investigation using electrostatic force microscopy - Longo, V. M.; Monteiro, V. F.; Pinheiro, A. S.; Terci, D.; Vasconcelos, J. S.; Paskocimas, C. A.; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Wiley, 2006)
A new method for high-resolution analyses of hair surface charge density under ambient conditions is presented in this paper. Electrostatic force microscopy (EFM) is used here to analyze changes in surface charge density in virgin hair, bleached hair, and hair treated with a cationic polymer. The atomic force microscopy technique is used concomitantly to analyze morphological changes in hair roughness and thickness. The EFM images depict exactly how the polymer is distributed on the surface of the hair fiber. The EFM's powerful analytical tools enabled us to evaluate the varying degrees of interaction between the hair fiber surface charge density and the cationic polymer. The surface charge density and the polymer's distribution in the hair fibers are presented in the light of EFM measurements. © 2006 Society of Cosmetic Scientists and the Socièété Française de Cosmétologie.
Keywords: Atomic force microscopy; Charge; Cosmetic; Hair; Microscopy; Polymer; Surface; bleaching; electrostatic force microscopy; evaluation; hair analysis; human; image analysis; measurement; microscopy; optical resolution; polymerization; surface charge; surface tension